Analysis of Factors that Influence the Quality of Work Life on the Performance of Specialist Doctors - Rini Astuti Wardhani; Ratno Adrianto; Iwan Muhammad Ramdan; Irfansyah Baharuddin Pakki; Iriyani Kamaruddin; Riyan Ningsih (GLOBAL HEALTH SCIENCE GROUP, 2026)
Performance (task performance) is the behavior of employees who are directly involved in forming organizational resources into goods or services that produce the organization, with attitudes and behavior that support the managerial, social, and psychological environment of an organization as contextual performance. There has been a decline in performance at the Kundungga Regional Hospital in 2022/2023 with various indicators, all of which impact decreasing public satisfaction with the quality of doctors' performance. This study aims to analyze the factors that influence Quality of Work Life (QWL) on the performance of specialist doctors at Kudungga Regional Hospital, East Kutai Regency. Analytical survey research with a cross-sectional approach was conducted in January 2024 on 37 respondents (total sampling). The measuring instruments used consist of doctor involvement, balanced compensation, job security, work environment safety, pride in the institution, career development, available facilities, problem-solving, communication, patient care, medical knowledge, practice-based learning, skills communication, professionalism, data analysis using the Spearman Rank Test with a confidence level of 95%. It was concluded that there was a relationship between compensation (p=0.043; R=0.489), patient care (p=0.000; R=0.072), medical knowledge (p=0.000, R=0.301), practice-based learning (p=0.000, R=- 0.053), communication skills (p=0.000, R=0.313) and professionalism (p=0.000, R=0.243) with the performance of specialist doctors at Kundungga Regional Hospital. Hospital Management is advised to pay more attention to balanced compensation factors, and services, increasing the amount of Income Improvement Allowance which is expected to improve the performance of Specialist Doctors at Kudungga Regional Hospital.